Climate change-induced droughts and tourism: Impacts and responses of Western Cape province, South Africa. (September 2022) - Dube, Kaitano; Nhamo, Godwell; Chikodzi, David
Abstract: Climate change has led to several extreme weather events across the world. One such weather extreme is drought. Drought phenomenon has been increasing in both frequency and intensity globally of late. To this end, there has been growing concern about the impact droughts have and will have on the tourist destinations in sub-Saharan Africa and beyond. In this study, which employs a mixed-methods approach utilising primary, archival and secondary data, we examine the impact of the 2015–2018 drought episodes on the tourism industry in the Western Cape as well as the industry's response. These drought episodes famously led to the Day Zero phenomenon, a situation that could have resulted in taps running dry at some point. The study found that the drought led to a severe decline in tourist arrivals at the major tourist attractions in the Western Cape province as well as a decline in tourist spending and hotel occupancy. This resulted in a loss of potential revenue and jobs. The province had been experiencing a decline in rainfall that drastically affected water supplies; a trend likely to recur in the future. During and after the drought, the tourism industry adopted several measures aimed at augmenting and saving water, thereby easing the sector's water demand. We recommend that the tourism sector and the Western Cape province build on the successes and lessons learnt during the Day Zero campaign to prepare for the future. This would allow the province to address Sustainable Development Goal 6, focusing on water and sanitation as a part of embracing responsible and sustainable tourism. Hence, continuous research, innovation and investment in the water-smart industry is a must for Cape Town and the Western Cape province. Management Implications: There is an increasing demand for the sector to improve water efficiency and security. There is a need for the tourism industry to develop models for managing droughts. Western Cape provides critical lessons on combating drought within the tourism sector. Tourism needs to invest in water harvest technology to ensure water independency. Tourism and recreation must adapt and mitigate climate change to ensure sector resilience.